Factor associated with physical activity level among secondary boarding school students in Selangor, Malaysia - Hisamuddin, Ahmad ‘Afifu’d-din; Saad, Hazizi Abu (Intelektual Pustaka Media Utama, 2025)
This cross-sectional study aimed to assess the prevalence and factors associated with physical activity among secondary boarding school students. Data were collected using a self-administered questionnaire that captured socio-demographic information, physical activity levels, sedentary behavior, social support (from family and peers), and psychological factors (depression, anxiety, and stress). Anthropometric measurements, including height and weight, were obtained using a SECA217 stadiometer and a Tanita weighing scale, with body mass index (BMI)-for-age subsequently calculated. A total of 181 participants were included in the study. The results indicated that the majority of students met the recommended physical activity guidelines. Approximately two-thirds of participants were classified as having a normal BMI, while the majority exhibited high levels of sedentary behavior. Regarding social support, only one-fifth of students reported receiving adequate family support, while half of the students reported adequate peer support. Psychological assessments revealed that one-third of participants exhibited normal depressive symptoms, whereas nearly half exhibited symptoms of anxiety and stress. Significant associations were identified between physical activity levels and several factors, including age, gender, family support, peer support, and stress. In conclusion, while most secondary boarding school students in this study met the recommended daily amount of physical activity, high levels of sedentary behavior and varying levels of social support and psychological distress highlight areas that warrant further intervention.